Bending wrinkling and kink behaviors of inflated beam under local uniform loadings. (January 2017) - Wang, C.G.; Liu, M.X.; Kang, J.T.; Xue, Z.M.; Tan, H.F.
Abstract: In this paper, analysis of the wrinkling and kink characteristics of the inflated beam under local uniform loadings is presented. Firstly the thin-walled beam modal, which is filled with uniform internal pressure, is established. Next the local uniform loads are applied on the beam. This introduces the load geometric parameters to the equations to predict the wrinkling characteristics. Then the kink, which is similar to a plastic hinge, is assumed to describe the invalid state of the inflated beam for the first time. In order to verify the assumptions of the kink and the theoretical predictions of the wrinkling and kink characteristics, the non-contact experimental tests are performed. Moreover, the theoretical and experimental results, which include the initial wrinkling and kink positions, the critical wrinkling and kink loads, the wrinkling strain, the length of the wrinkled region and the kink angle, are compared. The differences according to these comparisons are less than 10%, which means that the predicted results are reliable. In addition, the local uniform load position and its length as well as the edge shape and the middle cylinder length of the inflated beam can make great effects on the wrinkling and kink characteristics. These obtained results provide a new insight into the wrinkling and kink behaviors of the inflated beam and give good guidance for designing the inflated structures.